Increased economic salience or blurring of responsibility? Economic voting during the Great Recession - Lobo, Marina Costa (2020)
There is a puzzle which emerged following the Eurozone crisis: whereas the salience of the economy suggests an increase in economic voting, the realization that economic policies have become Europeanised may blur the responsibility of national governments, thus decreasing economic perceptions' weight on electoral choices. Do these mechanisms exclude each other? Do they refer to different groups of the electorate? We first examine the longitudinal trends of economic voting from 2002 to 2015 in three bailed out countries, namely Ireland, Portugal and Spain, to see if the economy's salience during the Great Recession increased the relevance of the economic perceptions in these countries. Secondly, making use of a unique media dataset of the last 16 years we test whether exposure to major mainstream newspapers that focus on the EU mitigates economic voting. On average, economic voting increased following the crisis. However, individuals who are more informed about the EU tend to use economic voting to a lesser extent, given they are more aware of the national government's limited room for manoeuvre.